A template/electrochemical deposition method for fabricating silver nanorod arrays based on porous anodic alumina. (4th July 2017) - Li, Yafang; Xu, Jie; Liu, Hao; Song, Jinzhong; Li, Yashuang; Cheng, Bowen; Li, Jin; Li, Xiaojiu
A template/electrochemical deposition method for fabricating silver nanorod arrays based on porous anodic alumina was presented. The barrier layer of porous anodic alumina templates was thinned by step-by-step voltage decrement method. Subsequently, silver ions were reduced into the channels of porous anodic alumina templates by electrochemical deposition method. Electrochemical impedance spectroscopy was utilized for analyzing the thickness of barrier layer of porous anodic alumina templates; the elementary composition and the size of silver nanorod arrays were characterized by X-ray diffraction and field-emission scanning electron microscope, respectively. Experimental results showed that the thickness of barrier layer of porous anodic alumina was suitable for alternating current electrochemical deposition, when anodizing potential was decreased to 70 V and widening time of porous anodic alumina in H3 PO4 solution is 80 min. And the silver particles could be deposited into the channels of porous anodic alumina templates at 11 V, 13 V, and 15 V. Different sizes of silver nanorod arrays were obtained by controlling the deposition time. The average diameter of silver nanorod is in the range from 346 nm to 351 nm which is almost consistent with the pore diameter of porous anodic alumina templates (367 nm). The uniform silver nanorod arrays have a considerable potential in the flexible and wearable electronic devices, optics, solar cell, the catalytical electrode, and so on.